“Coaching Boys into Men”: A Cluster-Randomized Controlled Trial of a Dating Violence Prevention Program - Miller, Elizabeth; Tancredi, Daniel J.; McCauley, Heather L.; Decker, Michele R.; Virata, Maria Catrina D.; Anderson, Heather A.; Stetkevich, Nicholas; Brown, Ernest W.; Moideen, Feroz; Silverman, Jay G. (Journal of adolescent health, 2012)
Dating violence (DV)—physical, sexual, and psychological aggression in adolescent romantic relationships—is prevalent among youth. Despite broad calls for primary prevention, few programs with demonstrated effectiveness exist. This cluster-randomized trial examined the effectiveness of a DV perpetration prevention program targeting coaches and high school male athletes. The unit of randomization was the high school (16 schools), and the unit of analysis was the athlete (N = 2,006 students). Primary outcomes were intentions to intervene, recognition of abusive behaviors, and gender-equitable attitudes. Secondary outcomes explored bystander behaviors and abuse perpetration. Regression models for clustered, longitudinal data assessed between-arm differences in over-time changes in mean levels of continuous outcomes in 1,798 athletes followed up at 3 months. Intervention athletes' changes in intentions to intervene were positive compared with control subjects, resulting in an estimated intervention effect of .12 (95% CI: .003, .24). Intervention athletes also reported higher levels of positive bystander intervention behavior than control subjects (.25, 95% CI: .13, .38). Changes in gender-equitable attitudes, recognition of abusive behaviors, and DV perpetration were not significant. Secondary analyses estimated intervention impacts according to intensity of program implementation. Compared with control subjects, athletes exposed to full-intensity implementation of the intervention demonstrated improvements in intentions to intervene (.16, 95% CI: .04, .27), recognition of abusive behaviors (.13, 95% CI: .003, .25), and positive bystander intervention (.28, 95% CI: .14, .41). This cluster-randomized controlled trial supports the effectiveness of a school athletics-based prevention program as one promising strategy to reduce DV perpetration.